(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
Referring to contemporary theories of citation, as well as to certain poststructuralist theories of intertextuality (Kristeva, Barthes), and especially to distinctive marks of transtextuality which were given by Genette, this paper examines the role and the function of biblical citations in the travels Seven Seas and Three Oceans by Serbian author Jelena Dimitrijević. The paper points to the paratextual aspects and the intertextual connections of the travels with the Bible as well as with Lamartine’s Travel to East. A prompt evocation of relevant passages from the Bible, which follow the chronology of author’s visits to holy places in Egypt, Palestine and Syria, provides an authentic referential illusion for the readers, an effect of a truthful, vital and dramatic experience. The historical discourse blends into the biblical one, the past blends with the presence, the sensuous eyes nurture the spiritual ones, triumphing in the religious trance and the power of imagination. Finally, the paper shows how a mosaic of biblical citations and references, which Jelena Dimitrijević refigures in her travels, integrates completely in the illustrative type of citation which represents the family, national and cultural tradition.